An Improved Cognitive Radio Spectrum Sensing Algorithm - Dengyin Zhang; Kuankuan Li; Li Xiao (Institute of Advanced Engineering and Science, 2013)
To improve the cognitive radio user’s detection performance and reduce the complexity, this paper composites the Fractal box dimension algorithm and the 3th-order cyclic-cumulate (TCC) algorithm and improves the TCC algorithm, so a novel detection algorithm is proposed that the Fractal box dimension is used when the signal to noise (SNR) is high, while the improved TCC algorithm is used when the SNR is low. This new algorithm not only avoids using TCC algorithm with high complexity when the channel environment is good, but also reduces the decision complexity of TCC algorithm. Simulation result shows that this algorithm obtains good detection performance with lower complexity than the traditional TCC algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1980